Dreaming is not enough. Audiovisual methodologies, social inclusion, and new forms of youth biopolitical resistance - Guerra, Paula; Sousa, Sofia (Frontiers in Sociology, 2022)
The eleventh Sustainable Development Goal, “make cities and human settlements inclusive, safe, resilient and sustainable,” can only be truly answered when there are no individuals in our societies who feel forgotten by the various social institutions. Not in Education, Employment, or Training [NEET] are among those most affected by this social invisibility. Nevertheless, these young people are not alienated or lost. Far from it. Instead, some of them found in the arts registered in the community—music, dance, photography and graffiti—a possibility to resist the various social stigmas attached on them. This was the view on which we conducted our artistic and social intervention, based on the innovative “arts-based research” methodology and “youth-led participatory research,” called “The Neighborhood is Ours II!,” with young NEETs in the socially underprivileged Cerco neighborhood of Porto in Portugal in 2022. We propose a theoretical-empirical approach around a visual/narrative sociology—namely using digital cinema—which will be based on a short film about the life narrative of a young NEET, who has used artistic practices to establish himself in the city of Porto as a cultural mediator. Thus—through these processes of co-creation of knowledge (cine-making)- we aim to demonstrate how the use of the arts can be a key tool in promoting social inclusion and reducing/minimizing feelings of insecurity, but also act as a means of resistance to the daily adversities experienced by marginalized young people and, of course, demonstrate the ways in which the use of artistic practices plays a pivotal role in the development of sustainable and alternative professional, social futures and citizenship.